Velocity of long bubbles transported by a liquid in horizontal channel - Hien, Ha Ngoc; Fabre, Jean (Vietnam Journal of Mechanics, 2010)
The influence of flowing liquid on the motion of long bubbles in horizontal channel is studied theoretically. The method of Benjamin (1968) is extended to the case of moving liquid: the liquid is inviscid, the surface tension is ignored and the liquid motion at infinity is characterized its velocity profile. The exact solutions for the bubble velocity and the liquid film thickness are given under an integral form. An approximate analytical solution can be found when the mean liquid velocity is weak enough versus the drift velocity. Two cases are investigated: the Couette flow and the Poiseuille flow. At first order, the two cases lead to identical solutions. The influence of the velocity distribution appears only at the second order.